Geo-analítica de apoyo a la gestión de inventarios en retail - caso de estudio en el sector ferretero del AMB (2019)
In traditional chain lines the retailer is the one in charge of managing the inventory. In these RMI (Retail managed inventory) systems, problems arise, mostly due to the lack of knowledge about demand. The use of GeoAnalytics can help us to make a more exhaustive analysis of this very important topic when it comes to making a good inventory management. Geo-Analytics allows us to know data such as: Location, quantity, and approximate amount of money spent on the product in question. You can also categorize your majority customers, identify them and focus on strengthening their loyalty with your product. In recent years a new system, the Vendor Managed Inventory, has been working. This system basically consists of the Supplier assuming the role of inventory manager and deciding how, how much and when orders will be placed. This helps reduce inventory costs for distributors, (Supplier customers). However, this new system, badly used, can lead to extra costs for suppliers, then becoming a system that all it does is transfer the costs from the distributor to the supplier, but not to reduce costs in the general chain of supplies. This project will focus on strengthening the Vendor Managed Inventory system using Analytical Geo as a tool to analyze demand and thus perform optimal inventory management, reducing the costs of supply chain members.